Education and responsibility - Romein, Tunis (The University Kentucky Press, 1955)
This book reveals the sources of the disquiet prevailing among educators over the apparent failure of the public school system to develop moral responsibility in America's youth. The doctrine of separation of church and state has made sectarian religious training illegal in public schools, and Tunis Romein shows that the task of providing moral guidance, suddenly thrust upon educators, has disclosed their deep schisms in educational philosophy -- basic contradictions which have split American education from top to bottom.